A road to development? Rural perspectives on infrastructure maintenance in Solomon Islands. Issue 6 (18th August 2019) - Hobbis, Stephanie Ketterer
ABSTRACT: The Solomon Islands Government and its development partners are heavily investing in road maintenance programmes to promote development in the small islands least developed state. Based on 12 months of ethnographic fieldwork, this article challenges the future orientation of these programmes. Instead it emphasises rural Solomon Islanders' past and present experiences with road-based mobilities and state-sponsored road maintenance projects. These experiences reveal roads and road repairs as a source of insecurity, immorality, and potential state violence that sideline, if not obstruct, hopes for any imagined future that a maintained road may (or may not) bring.